PENGARUH PARKIR PADA BADAN JALAN TERHADAP KINERJA RUAS JALAN K.H KHALID KOTA SAMARINDA - Anggraini, Mega Puspa (KURVA S JURNAL MAHASISWA, 2014)
Transportation problems are often encountered in the Samarinda city is the limited road space needed for traffic flow. Those problems are compounded by the fact that many roads are operating with much lower capacity than the capacity that should and the cause is the activity of on street parking.Parking facilities are elements that can not be separated froam the road transport system as a whole. With the increasing population of the city will increase the need for a wide range of activities. Most people do activities or travel by using private vehicles thus indirectly the necessary amount sufficient parking space. The use of the road as a parking lot is one of the main sources of local revenue so that the parking policy should be directed in addition to the advantages and disadvantages of road users either parking or passing on the road.In this study, which will be examined is how big vehicle operating costs that will be borne by motorists passing due to the on street parking.